Births and induced abortions among women of Russian, Somali and Kurdish origin, and the general population in Finland –comparison of self-reported and register data - Jokela, Satu (BMC Pregnancy Childbirth, 2018)
BACKGROUND: Since reproductive health is often considered a highly sensitive topic, underreporting in surveys and under coverage of register data occurs frequently. This may lead to inaccurate information about the reproductive health. This study compares the proportion of women having births and induced abortions among migrant women of Russian, Somali and Kurdish origin in Finland to women in the general Finnish population and examines the agreement between survey- and register-based data. METHODS: The survey data from the Migrant Health and Wellbeing Study conducted in 2010–2012 and data from the Health 2011 Survey with corresponding information on women in the general population were used in this study. The respondents were women aged 18–64: 341 Russian, 176 Somali and 228 Kurdish origin women and 630 women in the general population. The survey data were linked to the Finnish Medical Birth Register and the Register of Induced Abortions. RESULTS: In the combined (survey and register) data, migrant groups aged 30–64 had a higher proportion (89–96%) compared to the general population (69%) of women with at least one birth. Under-coverage of registered births was observed in all study groups. Among women aged 18–64, 36% of the Russian group and 24% of the Kurdish group reported more births in the survey than in the register data. In the combined data, the proportions of Russian origin (69%) and Kurdish origin (38%) women who have had at least one induced abortion in their lifetime are higher than in the general population (21%). Under-reporting of induced abortions in survey was observed among Somali origin women aged 18–29 (1% vs. 18%). The level of agreement between survey and register data was the lowest for induced abortions among the Somali and Russian groups (− 0.01 and 0.27). CONCLUSION: Both survey- and register-based information are needed in studies on reproductive health, especially when comparing women with foreign origin with women in the general population. Culturally sensitive survey protocols need to be developed to reduce reporting bias.